x-1分之x-1=x+2分之3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 22:14:46
x-1分之x-1=x+2分之3x-1分之x-1=x+2分之3x-1分之x-1=x+2分之3(x-1)分之(x-1)=(x+2)分之3∴1(X≠1)=(x+2)分之3X=1不成立(x-1)分之x-1=(
x-1分之x-1=x+2分之3
x-1分之x-1=x+2分之3
x-1分之x-1=x+2分之3
(x-1)分之(x-1)=(x+2)分之3
∴ 1(X≠1) =(x+2)分之3 X=1 不成立
(x-1)分之x-1=(x+2)分之3
通分得(x-1)分之1=(x+2)分之3
x+2=3x-3 ∴x=5/2
(x-1)/(x-1)=3/(x+2)---------1=3/(x+2)-----------x+2=3--------x=1
x²+x分之2+x²-x分之3=x平方-1分之4
x-1分之x-1=x+2分之3
X-3分之1=2+ 3-X分之X
6分之x-2=x分之x+3-1
(x+2)分之(x+1)-(x+7)分之1=(x+3)分之(x+2)-(x+6)分之1
x-2分之x-(x-2)(x-3)分之1-x的平方=x-3分之2x
(x+2分之3x-x+2分之x)/x平方-4分之x(x-1)=4
【化简求值】(x分之x+2 - x-2分之x-1)÷x分之x-4【化简求值】(x分之x+2 - x-2分之x-1)÷x分之x-4x=3
(x-1分之2x-x+1分之3x)除以x^2-1分之x
(x-1分之2x - x+1分之x)×x分之x²-1=
3分之2x+2分之1x十7分之1x+x=33
(x+1)分之3x+2x分之(x+1)=2分之5
11分之X-9-3分之X+2=1-X-2分之X-2
6分之X-9-3分之2+X=(x-1) -2分之X-2
1×2分之x+2×3分之x.+2003×2004分之x=2003 求x
1*2分之x+2*3分之x+.2008*2009分之x=2008,求x
x(x+1)分之1+(x+1)(x+2)分之1+(x+2)(x+3)分之1+.+(x+2010)(x+2011)分之1 x=1
已知x=100,求x(x+1)分之1+(x+1)(x+2)分之1+(x+2)(x+3)分之1+.+(x+99)(x+100)分之1